L’emigrazione italiana in Guatemala attraverso la letteratura (Altre Modernità, 2009)
From different perspectives, the lecture means to focus on the peculiar experience and complications of Italian emigration in Guatemala, mostly at the beginning of the last century, and its literary reading. Contemporary writers have often approached the theme of desplacement and uprooting in America, but it's quite unusual to find a voice who tells stories about small communities of emigrants. This is the case of Italians in Guatemala, whose cultural identity has been represented in the latest novel of Dante Liano. By analyzing his work, we try to speculate about the links among history, biography, exile and literary creation.
Keywords: Guatemala; Italy; emigration; identity; Dante Liano